INCREASE IN THE INCIDENCE OF ADOLESCENT VAGINAL DISCHARGE WITH LOW KNOWLEDGE, ATTITUDES AND BEHAVIORS OF VAGINAL HYGIENE - Sri Mulyanti; Nabila Meisyenur; Heri Budiawan; Ubad Badrudin (Poltekkes Kemenkes Bandung, 2025)
Vaginal discharge, also known medically as Fluor Albus, is excessive discharge from the vagina. The prevalence of adolescent girls who experience vaginal discharge is still quite high in Indonesia. This may be due to a lack of information about vaginal discharge. Vaginal discharge causes discomfort and has an impact on self-confidence in adolescents. Therefore, the knowledge of adolescents about vaginal discharge is very important to change the attitude and behavior of clean and healthy living. This study aimed to determine the relationship between knowledge, attitude, and vaginal hygiene behavior with the incidence of vaginal discharge. This study was a quantitative study using a cross-sectional analytic survey research design. A sample of 115 people was obtained using the total sampling technique. The total sampling method can reflect the condition of the population accurately and thoroughly. The data collection process used a questionnaire and was analyzed by frequency distribution and chi-square test. It showed that 55.7% of respondents had poor knowledge, 65.2% had poor attitudes, and 64.3% had poor behavior. In the Chi-Square test, it was found that there was a relationship between knowledge, attitude, and vaginal hygiene behavior with the incidence of vaginal discharge at MTs Persis 07 Cempakawarna (p = <0.001). It can be concluded that there is a relationship between knowledge, attitude, and vaginal hygiene behavior. Therefore, it is recommended to increase knowledge, attitudes, and behavior of vaginal hygiene to prevent the occurrence of vaginal discharge.